Targeting the B1 Gene and Analysis of Its Polymorphism Associated with Awned/Awnless Trait in Russian Germplasm Collections of Common Wheat - Andrey B. Shcherban (MDPI AG, 2021)
The presence of awns on the ear is associated with a number of important plant properties, such as drought resistance, quality of the grain mass during processing, etc. The main manifestations of this trait are controlled by the B1 gene, which has recently been identified and encodes the C2H2 zinc finger transcription factor. Based on the previously identified SNPs in the promoter region of this gene, we constructed markers for dominant and recessive alleles which determine awnless and awned phenotypes, respectively. The markers were successful for use in targeting the respective alleles of the B1 gene in 176 varieties of common wheat, accessions of T. spelta L., as well as on F2/F3 hybrids from crosses between awned and awnless forms of T. aestivum. We first identified a new allele, b1mite, which has both an insert of a miniature Stowaway-like transposon, 261 bp in length, and 33 novel SNPs in the promoter region. Despite these changes, this allele had no effect on the awned phenotype. The possible mechanisms of the influence of the analyzed gene on phenotype are discussed.